1989
DOI: 10.1084/jem.170.3.797
|View full text |Cite
|
Sign up to set email alerts
|

Lysis of human melanoma cells by autologous cytolytic T cell clones. Identification of human histocompatibility leukocyte antigen A2 as a restriction element for three different antigens.

Abstract: From the peripheral blood of the melanoma patient (AV), we derived cytolytic T lymphocyte (CTL) clones that lysed the autologous tumor line SK-MEL-29, but not autologous EBV-B cells, K562, and other tumor targets. By immunoselection experiments it was shown that the CTL clones recognized at least three different antigens on the autologous tumor cells. We demonstrate here that these melanoma antigens are presented to the CTL in association with HLA-A2. First, HLA-A2-reactive pregnancy sera as well as an mAb aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
80
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(83 citation statements)
references
References 50 publications
3
80
0
Order By: Relevance
“…While TIL 1143 lysed all 3 Ewing's sarcomas, the multiple specificities of this polyclonal culture complicate interpretations of tumor antigen sharing. Individual melanoma lines have been shown to express multiple distinct tumor antigens recognized by specific CTL [21,22,27,29]. Thus, while our polyclonal TIL cultures are all capable of specifically recognizing the HLA-A2 + melanomas 501-mel, 624-mcl, and a variety of others, they do not necessarily react with a single tumor antigen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While TIL 1143 lysed all 3 Ewing's sarcomas, the multiple specificities of this polyclonal culture complicate interpretations of tumor antigen sharing. Individual melanoma lines have been shown to express multiple distinct tumor antigens recognized by specific CTL [21,22,27,29]. Thus, while our polyclonal TIL cultures are all capable of specifically recognizing the HLA-A2 + melanomas 501-mel, 624-mcl, and a variety of others, they do not necessarily react with a single tumor antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Cytolytic T cells can recognize commonly expressed melanoma-associated antigens in the context of a variety of HLA-A, -B, and -C, molecules [5,6,9,10,17,28,29]. Such MHC-class-I-restricted T cells have also been shown to recognize cultured normal melanocytes [1], suggesting targeting of a differentiation antigen.…”
Section: Discussionmentioning
confidence: 99%
“…C ytotoxic T lymphocytes recognize protein Ags as small peptide products of cytoplasmic proteolysis bound to MHC molecules (1,2). Epitope peptide binding to specific HLA isotypes is determined by definite consensus motifs present in the amino acid sequences of the Ag peptides (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…Epitope peptide binding to specific HLA isotypes is determined by definite consensus motifs present in the amino acid sequences of the Ag peptides (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…Work by Kawakami et al (24) demonstrated the presence of multiple peptide specificities within therapeutic cytotoxic tumor-infiltrating lymphocytes, demonstrating the potential diversity of the in vivo CTL response against melanoma. In other studies, using T cell clones or Ag loss tumor variants, it has been established that multiple specificities exist in CTL lines induced in vitro after stimulation with tumor cells (31)(32)(33). Tüting et al (34), utilizing autologous DC transfected with one or multiple cDNAs encoding melanoma TAA to stimulate PBL from normal donors, demonstrated TAA peptide-specific CTL reactivity.…”
Section: Discussionmentioning
confidence: 99%